Developing and implementing models for the prevalence, incidence and geographic spread of opiate use in Ireland - Dempsey, Orla (Trinity College (Dublin, Ireland). School of Nursing & Midwifery, 2011)
The objective of this study is to further develop and implement established mathematical models for the first time to the problem of estimating the true size of the opiate epidemic and to develop and apply existing mathematical models to the problem of modelling the geographic spread of opiate use in Ireland. Estimates of the true size and spread of the opiate epidemic are difficult to obtain due to the hidden nature of opiate use however these estimates are vital for policy makers and service providers when planning for the provision of effective treatment services. In a bid to estimate the true size of the epidemic this research focuses on deriving suitable models to estimate the prevalence and incidence of opiate use in Ireland.
Keywords: Nursing and Midwifery, Ph.D.; Ph.D. Trinity College Dublin